Modelagem e controle robusto de sistema de Pitch e turbinas eólicas - Rodrigues, Michel Ney de Almeida Barroso (2022)
The present work presents the establishment of a simulator for position and speed control loops in wind turbines pitch systems which uses DC motors to rotate their blades along with a non-linear controller proposal to replace the classical speed regulator. To assess the simulator’s efficacy there were graphical and statistical comparisons between the simulator’s resulting signal and its pair from field measurements. The non-linear controller structure is built around a state feedback with integral action to allow a reference tracking and disturbances compensations. It was also added a H∞ norm and D-stability to, respectively, minimize a second state from the plant and grant more degrees of freedom for pole allocation through a solution of Linear Matrices Inequalities. In all scenarios the proposed control resulted in an agile reference tracking in addition to minimizing the required electrical current to counterpart the disturbances